Impatiens Downy Mildew - Laura Warner; Bill Schall; Aaron J. Palmateer; Natalia A. Peres (EDIS)
Downy mildew on impatiens is of great concern throughout Florida. Winters in south Florida provide high humidity paired with cool nights, creating ideal conditions for disease development. Downy mildews are caused by several different species of pathogens that tend to be plant-host specific. Plasmopara obducens is the pathogen that affects impatiens. Some literature indicates that nighttime temperatures of about 50 to 72°F favor downy mildew, but the disease has been reported on impatiens year-round in south Florida. This 4-page fact sheet was written by L. Sanagorski (Warner), B. Schall, A.J. Palmateer, and N.A. Peres, and published by the UF Department of Plant Pathology, October 2013.